2020
DOI: 10.1042/bsr20200980
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognosis-related genes in the tumor microenvironment of stomach adenocarcinoma by TCGA and GEO datasets

Abstract: Accumulating evidence has demonstrated that tumor microenvironment (TME) plays a crucial role in stomach adenocarcinoma (STAD) development, progression, prognosis and immunotherapeutic responses. How the genes in TME interact and behave is extremely crucial for tumor investigation. In the present study, we used gene expression data of STAD available from TCGA and GEO datasets to infer tumor purity using ESTIMATE algorithms, and predicted the associations between tumor purity and clinical features and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…The tumor microenvironment significantly contributes to the occurrence, progression, prognosis, and immunotherapy response of gastric adenocarcinoma. 6 Gastric adenocarcinoma is a chronic gastritis caused by Helicobacter pylori and is often characterized by the infiltration of immune cells, including granulocytes, macrophages, and T lymphocytes. 40 Therefore, the current study explored the relationship between prognostic risk and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor microenvironment significantly contributes to the occurrence, progression, prognosis, and immunotherapy response of gastric adenocarcinoma. 6 Gastric adenocarcinoma is a chronic gastritis caused by Helicobacter pylori and is often characterized by the infiltration of immune cells, including granulocytes, macrophages, and T lymphocytes. 40 Therefore, the current study explored the relationship between prognostic risk and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Therefore, numerous studies have been conducted to explore prognostic biomarkers in an attempt to improve the clinical outcome of patients with gastric adenocarcinoma. Among them, Yao and Ren et al evaluated the importance of immune microenvironment‐related genes in gastric adenocarcinoma prognosis by mining public databases 5 , 6 . However, a more comprehensive understanding of tumorigenesis mechanisms and the exploration of potential prognostic biomarkers from multiple perspectives are still required.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been proposed that tumor microenvironments, especially immune factors within such environments, play an important role in STAD progression 41 , 42 . Accumulating evidence indicates that tumor microenvironment immune subtypes can predict clinical responses to immunotherapeutic strategies across a variety of tumor types 41 , 43 . The present study demonstrated that high RASGRF2 expression correlates significantly and positively with gene signature-estimated Tem, macrophage, pDC, and NK cell infiltration into the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The TCGA is well-established as the most comprehensive cancer genomics program, which has produced, evaluated, and made public data related to the genomic sequencing, expression, methylation, and copy number variation of over 11,000 patients with cancer who have been diagnosed with more than 30 distinct forms of cancer (17). Many previous bioinformatics studies have followed the traditional study design of analyzing the TCGA data and followed by the verification of the computationally predicted results using GEO data sets (19)(20)(21)(22)(23)(24). The GEO database is a freely accessible resource for the functional genomics data that contain original data sets from tens of thousands of published microarray or sequencing experiments (25).…”
Section: Introductionmentioning
confidence: 99%